Influence of radial depth of cut on entry conditions and dynamics in face milling application - Agic, A.; Eynian, M.; Hägglund, S.; Ståhl, J.-E.; Beno, T. (Сверхтвердые материалы, 2017)
In this study, acceleration of the workpiece is measured for different radial depths of cut and cutting edge geometries. The influence of the radial depth of cut on the dynamical behavior is evaluated in time and frequency domains. The results for different radial depths of cut and cutting geometries are quantified using the root mean square value of acceleration. The outcome of this research study can be used both for the better cutting data recommendations and improved tool design.